Enhancing AQM Performance on Wireless Networks - HUGGARD, MERIEL; MC GOLDRICK, CIARAN SEAMUS; PIBIRI, GIANLUIGI (IEEE, 2013)
Congestion management is a key factor in the provision of acceptable levels of quality of service (QoS) on wired networks. However, the concept of congestion management does not translate easily into the wireless domain. Active Queue Management (AQM) solutions for congestion avoidance have proved effective in wired networks but have not gained much traction in the wireless world. Wireless AQM schemes need to be capable of being easily scaled in order to maintain the algorithm characteristics and improve their efficiency. The RED, REM and BLUE AQM schemes are considered from a wireless perspective and methods for improving their efficiency and performance in wireless networks are given.
IEEE IFIP Wireless Days
PUBLISHED
Keywords: Wireless Network AQM